High-toughness antibacterial hemostatic chitosan hydrogel dressing and preparation method thereof
By introducing vinyl cerium oxide nanoparticles and methacrylylated chitosan into chitosan hydrogel, a high-strength antibacterial hemostatic hydrogel dressing was prepared, which solved the shortcomings of existing dressings in terms of mechanical strength and antibacterial and anti-inflammatory properties, and achieved effective healing of chronic wounds in diabetes.
Patent Information
- Application Number
- CN202510209276.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing diabetic chronic wound dressings have shortcomings in terms of mechanical strength and antibacterial and anti-inflammatory properties, and cannot effectively deal with the challenges of severe bacterial infection and wound healing.
By introducing vinyl cerium oxide nanoparticles as crosslinking agents into chitosan hydrogels, combined with methacrylylated chitosan as the main body, a hydrogel dressing with excellent mechanical properties and antibacterial hemostatic function was prepared using free radical polymerization technology.
The high-strength toughness and anti-circulation loading ability of hydrogel dressings are achieved, which significantly improves its application effect on chronic wounds of diabetes and has good biocompatibility and therapeutic effects.
Smart Images

Figure CN119680004A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials and relates to a high-strength antibacterial hemostatic chitosan hydrogel dressing and a preparation method thereof. Background Art
[0002] The healing of chronic diabetic wounds is a complex and challenging process. The main obstacles are high blood sugar, high oxidative stress, excessive inflammatory response, and lack of oxygen and nutrients in tissues. These factors work together to damage the repair mechanism and make the wound healing very slow. When the wound is complicated by bacterial infection, the situation worsens further, which not only aggravates the problem of the wound itself, but also may prolong the time of non-healing. Traditional dressings such as vaseline gauze are unable to maintain a moist environment on the wound and lack biological activity, so they have limited effect in promoting wound healing.
[0003] To address these issues, researchers began to explore the application of new materials, among which natural polysaccharide hydrogels stand out due to their good biocompatibility. This type of material can keep the wound moist, which is conducive to cell proliferation and migration, and accelerates the healing process. For wounds with complications of infection, dressings containing antibiotics or metallic silver ions are usually used to control the infection. However, this strategy is not without disadvantages: the widespread use of antibiotics may lead to the emergence of drug-resistant strains, and although metallic silver ions have strong antibacterial properties, they also have the risk of toxicity to healthy cells, which shows that it is crucial to develop an antibacterial dressing that is both safe and effective.
[0004] Chitosan and its derivatives, as a special class of polycationic polysaccharides, have been proven to be one of the ideal choices for wound repair materials due to their excellent antibacterial and hemostatic properties. They can not only effectively fight pathogenic microorganisms, but also accelerate blood coagulation and reduce bleeding, which is particularly important for treating chronic wounds in diabetic patients. However, for wounds with severe bacterial infections, chitosan alone still cannot meet the requirements of antibacterial and anti-inflammatory. In addition, existing polysaccharide hydrogel dressings also face a common problem-insufficient mechanical strength. Under the pressure conditions unique to diabetic wounds, the hydrogel network structure is easily destroyed, which seriously affects the actual application effect of the dressing. In order to overcome this limitation, improving the mechanical properties of the material and making it more adaptable to the mechanical environment of the wound has become a key issue that needs to be urgently solved in current clinical treatment.
[0005] A Chinese patent application document (publication number: CN109627462A) discloses a method for preparing a high-strength methacrylated chitosan hydrogel. The method obtains a high-elasticity hydrogel with a compressive strength of 2-4 MPa by photocrosslinking water-soluble chitosan and F127 derivatives. However, the patent content does not involve the optimization of the biological functions of chitosan hydrogel materials, which greatly limits its use. Summary of the invention
[0006] The purpose of the present invention is to address the above problems existing in the prior art and to provide a high-strength and tough antibacterial and hemostatic chitosan hydrogel dressing with excellent biological functions.
[0007] The purpose of the present invention can be achieved by the following technical solutions: A high-strength antibacterial and hemostatic chitosan hydrogel dressing. The hydrogel dressing raw materials include vinyl cerium oxide nanoparticles and methacryloyl chitosan in a mass ratio of 1: (20-200).
[0008] The present invention selects vinyl rare earth cerium oxide as the cross-linking point and methacryloyl chitosan as the main body of the hydrogel dressing, and prepares the chitosan hydrogel dressing with excellent mechanical properties and antibacterial and hemostatic functions through free radical polymerization. When subjected to external stress, the cross-linked micro-nano particles can dissipate energy through deformation, unwinding, chain slippage, etc., so that the hydrogel exhibits excellent strength, toughness and resistance to cyclic loads.
[0009] In the above-mentioned high-strength antibacterial hemostatic chitosan hydrogel dressing, the preparation method of vinyl cerium oxide nanoparticles includes the following steps: dissolving cerium nitrate hexahydrate in a solvent and heating it, then adding ammonia water to obtain a cerium oxide dispersion, then adding vinyl triethoxysilane to react, and finally washing and cooling to obtain vinyl cerium oxide nanoparticles.
[0010] The advantages of using vinyl rare earth cerium oxide as a micro-nano particle cross-linking agent in the present invention are that, on the one hand, the micro-nano particles can significantly improve the mechanical strength of the hydrogel dressing as energy dissipation units; on the other hand, the rare earth cerium oxide with antibacterial and hemostatic properties is compounded with chitosan to synergistically enhance the biological function of the hydrogel dressing.
[0011] In the above-mentioned high-strength antibacterial hemostatic chitosan hydrogel dressing, the solvent is a mixed solution of water and an organic solvent in a volume ratio of 1: (0.5-1.5).
[0012] Preferably, the organic solvent includes, but is not limited to, one or more of methanol, ethanol, isopropanol, acetone, and the like.
[0013] In the above-mentioned high-strength antibacterial hemostatic chitosan hydrogel dressing, the added amount of vinyl triethoxy silane is 0.1-10 ml of vinyl triethoxy silane per gram of cerium nitrate hexahydrate.
[0014] Preferably, the amount of vinyltriethoxysilane added is 1.5-3.0 ml of vinyltriethoxysilane per gram of cerium nitrate hexahydrate.
[0015] In the above-mentioned high-strength antibacterial hemostatic chitosan hydrogel dressing, the reaction temperature is 50-70°C and the reaction time is 10-30 min.
[0016] In the above-mentioned high-strength antibacterial hemostatic chitosan hydrogel dressing, the particle size of the vinyl cerium oxide nanoparticles is 100-800 nm.
[0017] Preferably, the particle size of the vinyl cerium oxide nanoparticles is 200-400 nm. The present invention controls the particle size of the vinyl cerium oxide nanoparticles so that they have an optimal specific surface area, which not only increases the interaction between them and the chitosan molecular chain, but also makes them easier to be evenly dispersed in the hydrogel network. When the nanoparticles are evenly dispersed, the local stress concentration phenomenon caused by particle aggregation can be effectively avoided, thereby improving the uniformity and mechanical strength of the entire hydrogel structure.
[0018] In the above-mentioned high-strength antibacterial hemostatic chitosan hydrogel dressing, the methacrylylated chitosan is prepared by reacting chitosan with methacrylic anhydride to carry out double-bond functionalization modification.
[0019] Preferably, the preparation method of methacryloyl chitosan comprises the following steps: dissolving chitosan in water containing acetic acid, heating to 55-65°C, then adding methacrylic anhydride dropwise for reaction for 2-5 hours, then adjusting the pH value of the solution to 5-6.5, and finally dialyzing and drying to obtain methacryloyl chitosan.
[0020] In the above-mentioned high-toughness antibacterial hemostatic chitosan hydrogel dressing, the viscosity of chitosan is 100-200mPa s, and the degree of deacetylation is ≥95%. In the present invention, it is necessary to control the viscosity of chitosan. When the viscosity of chitosan is too low (i.e., the molecular weight is too low), the network structure formed by it is relatively loose, and it is unable to provide sufficient physical entanglement to enhance the mechanical strength of the hydrogel, causing the hydrogel to be easily broken or deformed when subjected to external forces, thereby affecting its practical application effect as a wound dressing. On the contrary, if the molecular weight of chitosan is too high, although it can theoretically provide stronger mechanical support, it actually brings about the problem of difficulty in dissolving. High molecular weight chitosan is difficult to fully dissolve in the solvent, which not only increases the difficulty of operation during the preparation process, but also may cause uneven dispersion and mixing, thereby affecting the overall performance and consistency of the material.
[0021] In the above-mentioned high-strength antibacterial and hemostatic chitosan hydrogel dressing, the double bond grafting rate of the methacrylylated chitosan is 5-20%.
[0022] The present invention also provides a method for preparing the above-mentioned high-strength antibacterial hemostatic chitosan hydrogel dressing, the method comprising the following steps: S1, dissolving methacryloyl chitosan and a photoinitiator in water to obtain a methacryloyl chitosan aqueous solution; S2, then ultrasonically dispersing the vinyl cerium oxide nanoparticles into a mixed solution of water and an organic solvent to obtain a mixed solution of vinyl cerium oxide nanoparticles; S3, stirring the methacrylylated chitosan aqueous solution and the vinyl cerium oxide nanoparticles mixed solution uniformly and then introducing nitrogen gas into the mixed solution to obtain a prepolymer solution; S3, photocuring the prepolymer solution to obtain chitosan hydrogel.
[0023] In the present invention, it is necessary to strictly control the addition amount of vinyl cerium oxide nanoparticles and methacryloyl chitosan, wherein excessive addition of vinyl cerium oxide nanoparticles will lead to uneven dispersion in the hydrogel network. When the concentration of nanoparticles is too high, they tend to aggregate to form clusters instead of being evenly distributed in the polymer matrix. This aggregation phenomenon not only weakens the effectiveness of the nanoparticles as cross-linking points, but also may cause local stress concentration, resulting in weak links in the hydrogel structure. If the addition amount of vinyl cerium oxide nanoparticles is insufficient, it will not be able to provide enough cross-linking points to significantly improve the mechanical strength of the hydrogel, which means that the material may lack the necessary support when facing external pressure or stretching, and it is difficult to meet the physical properties required for chronic wound care of diabetes. At the same time, an appropriate amount of nanoparticles is essential for synergistically improving the biological function of the hydrogel. Cerium oxide nanoparticles have good antibacterial properties and can inhibit bacterial growth by producing reactive oxygen species (ROS) or changing the permeability of bacterial cell membranes, while chitosan itself also has certain antibacterial and hemostatic properties. The two can produce a synergistic effect in a suitable proportion and jointly promote wound healing. However, if too little nanoparticles are added, this synergistic effect will be greatly reduced, affecting the overall therapeutic effect of the dressing.
[0024] Preferably, the concentration of methacryloylated chitosan in the methacryloylated chitosan aqueous solution in step S1 is 1-10% w / v.
[0025] In the above-mentioned method for preparing a high-strength antibacterial hemostatic chitosan hydrogel dressing, the mass ratio of the photoinitiator to the methacrylylated chitosan is 0.1-1:100.
[0026] Preferably, the photoinitiator is an ultraviolet photoinitiator.
[0027] More preferably, the ultraviolet light initiator is Irgacure 1173.
[0028] Preferably, the volume ratio of the methacrylylated chitosan aqueous solution to the vinyl cerium oxide nanoparticle mixed solution is 1:(0.5-1.5).
[0029] Preferably, the organic solvent in step S2 includes but is not limited to one or more of methanol, ethanol, isopropanol, acetone, etc.
[0030] Preferably, the curing is UV curing for 10-30 minutes.
[0031] More preferably, the UV curing intensity is 70-320 μW / cm².
[0032] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention successfully constructs a chitosan hydrogel dressing with excellent mechanical properties and antibacterial and hemostatic functions by introducing vinyl rare earth cerium oxide micro-nanoparticles as cross-linking agents into a polymer network. The micro-nanoparticles can dissipate energy through deformation, untangling and chain slippage when subjected to external stress, thereby giving the hydrogel dressing excellent strength, toughness and the ability to resist cyclic loads.
[0033] 2. The main advantage of the hydrogel dressing of the present invention is that it combines the energy dissipation properties of vinyl rare earth cerium oxide with the biological activity of cerium oxide and chitosan itself. On the one hand, the micro-nano-scale rare earth cerium oxide particles act as effective energy dissipation units, which greatly improves the mechanical strength of the hydrogel dressing; on the other hand, there is a synergistic effect between rare earth cerium oxide and chitosan, which enhances the antibacterial and hemostatic properties of the dressing. Therefore, the dressing can not only provide the necessary physical support for chronic diabetic wounds, but also has good biocompatibility and therapeutic effects, and is expected to significantly improve the healing process of infectious wounds.
[0034] 3. The present invention mixes two main components (methacrylylated chitosan and vinyl cerium oxide nanoparticles) and the photoinitiator Irgacure 1173 in proportion, stirs them evenly at room temperature, introduces nitrogen to remove oxygen, and then forms the final hydrogel dressing by UV curing. This preparation method not only simplifies the process steps, but also ensures the consistency of the material structure and the stability of the performance. UV curing is a fast and controllable process, which can complete the cross-linking reaction in a short time while maintaining the uniformity of the material, thereby ensuring the consistency of each batch of products. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a photo of the chitosan hydrogel prepared in Example 1.
[0036] Figure 2 The antibacterial properties of the chitosan hydrogel prepared in Example 1 and the blank control are demonstrated.
[0037] Figure 3 The in vitro coagulation performance of the chitosan hydrogel prepared in Example 1 and the blank control is demonstrated. DETAILED DESCRIPTION
[0038] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments. Example 1
[0039] S1. Mix 3 g chitosan, 4 mL acetic acid, and 300 mL deionized water and stir until chitosan is completely dissolved, heat to 60°C, then drop 14 mL methacrylic anhydride into the solution, and continue the reaction for 3 hours. After the reaction, drop sodium bicarbonate solution to adjust the pH value of the solution to weak acidity, dialyze the solution for 5 days, and then freeze-dry to obtain methacrylylated chitosan.
[0040] S2. Dissolve 2.6 g of cerium nitrate hexahydrate in 100 mL of water-ethanol (volume ratio 1:1) mixture, heat to 60°C and add 20 mL of ammonia water to obtain cerium oxide dispersion, then add 5 mL of vinyl triethoxysilane to the cerium oxide dispersion and continue to react for 15 minutes. After the reaction is completed, the solution is cooled to room temperature, the precipitate is washed with deionized water and anhydrous ethanol several times until it is neutral, and freeze-dried to obtain vinyl cerium oxide nanoparticles with a median particle size of 200 nm.
[0041] S3. Dissolve 1 g of methacryloyl chitosan and 5 mg of photoinitiator Irgacure 1173 in 5 mL of water, and ultrasonically disperse 0.01 g of vinyl cerium oxide nanoparticles in 5 mL of a water-ethanol (volume ratio 1:1) mixture. Mix the two thoroughly and stir them evenly, then introduce nitrogen bubbling for 15 minutes to remove oxygen in the system to obtain a prepolymer solution.
[0042] S4, inject the prepolymer liquid into the mold, UV-curing for 20 min, and remove the mold to obtain Figure 1 Chitosan hydrogel shown. Example 2
[0043] S1. Mix 6 g chitosan, 8 mL acetic acid, and 600 mL deionized water and stir until the chitosan is completely dissolved, heat to 60°C, then drop 8 mL methacrylic anhydride into the solution, and continue the reaction for 5 hours. After the reaction, drop sodium bicarbonate solution to adjust the pH value of the solution to weak acidity, dialyze the solution for 5 days, and then freeze-dry to obtain methacrylylated chitosan.
[0044] S2. Dissolve 5.2 g of cerium nitrate hexahydrate in 200 mL of a water-ethanol (volume ratio 1:1) mixture, heat to 60°C, add 15 mL of ammonia water to obtain a cerium oxide dispersion, continue to add 15 mL of vinyl triethoxysilane to the cerium oxide dispersion and continue to react for 15 minutes. After the reaction is completed, the solution is cooled to room temperature, and the precipitate is washed with deionized water and anhydrous ethanol several times until it is neutral, and freeze-dried to obtain vinyl cerium oxide nanoparticles.
[0045] S3. Dissolve 2 g of methacryloyl chitosan and 15 mg of photoinitiator Irgacure 1173 in 5 mL of water, and ultrasonically disperse 0.01 g of vinyl cerium oxide nanoparticles in 5 mL of a water-ethanol (volume ratio 1:1) mixture. Mix the two thoroughly and stir them evenly, then introduce nitrogen gas for 15 min to remove oxygen in the system to obtain a prepolymer solution.
[0046] S4. Inject the prepolymer solution into the mold and cure it under UV light for 30 min. After removing the mold, chitosan hydrogel is obtained. Example 3
[0047] S1. Mix 1g chitosan, 1mL acetic acid and 100mL deionized water and stir until chitosan is completely dissolved, heat to 60°C, then drop 5mL methacrylic anhydride into the solution and continue the reaction for 3 hours. After the reaction, drop sodium bicarbonate solution to adjust the pH value of the solution to weak acidity, dialyze the solution for 5 days and freeze-dry to obtain methacrylylated chitosan.
[0048] S2. Dissolve 2.6 g of cerium nitrate hexahydrate in 100 mL of a water-ethanol (volume ratio 1:1) mixture, heat to 60°C, add 20 mL of ammonia water to obtain a cerium oxide dispersion, continue to add 5 mL of vinyl triethoxysilane to the cerium oxide dispersion and continue to react for 15 minutes. After the reaction is completed, the solution is cooled to room temperature, and the precipitate is washed with deionized water and anhydrous ethanol several times until it is neutral, and freeze-dried to obtain vinyl cerium oxide nanoparticles.
[0049] S3. Dissolve 3 g of methacryloyl chitosan and 10 mg of photoinitiator Irgacure 1173 in 5 mL of water, and ultrasonically disperse 0.02 g of vinyl cerium oxide nanoparticles in 5 mL of a water-ethanol (volume ratio 1:1) mixture. Mix the two thoroughly and stir them evenly, then introduce nitrogen bubbling for 15 min to remove oxygen in the system to obtain a prepolymer solution.
[0050] S4. Inject the prepolymer solution into the mold and cure it under UV light for 30 min. After removing the mold, chitosan hydrogel is obtained.
[0051] Comparative Example 1: The only difference from Example 1 is that in step S3, the methacrylylated chitosan is replaced by chitosan without methacrylylation.
[0052] Since chitosan cannot be directly dissolved in water, the preparation cannot be carried out.
[0053] Comparative Example 2: The only difference from Example 1 is that in step S3, the vinyl cerium oxide nanoparticles are replaced by cerium oxide nanoparticles without vinyl functionalization.
[0054] Since they have not undergone vinyl functionalization, that is, there are no grafted double bonds, they cannot become cross-linking agents. Nanoparticles directly added to the system are only physically mixed, rather than acting as energy dissipators of cross-linking agents, which greatly reduces the mechanical strength of the hydrogel.
[0055] Comparative Example 3: The only difference from Example 1 is that the amount of vinyl cerium oxide nanoparticles added in step S3 is 0.001 g.
[0056] Due to the addition of too few vinyl cerium oxide nanoparticles, the cross-linking points formed are sparse and unevenly distributed, which not only weakens the internal network structure of the hydrogel, but also makes it easy to deform or break when subjected to external forces, resulting in a significant decrease in the overall mechanical strength, making it difficult to meet the physical properties required for the care of chronic diabetic wounds. Moreover, the number of nanoparticles is not enough to cover the entire hydrogel surface, and it cannot be evenly distributed in the wound area, which directly leads to a significant reduction in the antibacterial and hemostatic effects, greatly reducing the effectiveness of the dressing in treating infectious wounds.
[0057] Comparative Example 4: The only difference from Example 1 is that the amount of vinyl cerium oxide nanoparticles added in step S3 is 0.1 g.
[0058] Excess nanoparticles are unevenly dispersed in the system, resulting in the formation of hard areas inside the material, affecting the overall flexibility and adaptability of the hydrogel, making it difficult to conform to complex wound shapes in practical applications, and more likely to fail when faced with external pressure or stretching.
[0059] The analysis method in the examples of this application is as follows: Compression strength characterization. The shaped hydrogel was made into a disc with a diameter of 10 mm and a thickness of 2 mm, placed in a universal material testing machine, and subjected to compression testing at a rate of 10% strain / min. The compression strength of the sample was recorded. Figure 1 The chitosan hydrogel material prepared in Example 1 has a compressive strength of 2 MPa.
[0060] Characterization of antibacterial properties. The antibacterial properties of the prepared chitosan hydrogel were evaluated with reference to the industry standard WS / T 650 (Evaluation of antibacterial and antibacterial effects). The molded hydrogel was made into a disc with a diameter of 10 mm and a thickness of 2 mm. 5 CFU / mL Staphylococcus aureus was co-cultured for 6 hours, and the bacterial solution was diluted and plated for counting to observe the sterilization of the material. Among them, the blank group was the natural growth of bacteria, and the experimental group was the chitosan hydrogel prepared in Example 1. Figure 2As shown, there are a large number of bacteria in the blank group, and almost no bacteria in the experimental group, indicating that the chitosan hydrogel prepared by the present invention has excellent antibacterial properties.
[0061] In vitro coagulation performance characterization. At room temperature, chitosan hydrogel samples (5 mm diameter, 2 mm thick discs) were added to a centrifuge tube containing 100 µL of calcium-replenished blood. After incubation at 37 °C for 3 minutes, 500 mL of PBS was added and the color of the supernatant was observed to determine the coagulation status. The blank group was a natural coagulation group. Figure 3 As shown, after adding PBS to the blank group, the solution was turbid and no supernatant appeared, indicating that the blood did not coagulate within 3 minutes under natural conditions. After adding PBS to the chitosan hydrogel prepared in Example 1, the experimental group showed obvious upper and lower stratification, indicating that the blood in the lower layer had coagulated, indicating that the chitosan hydrogel material prepared by the present invention has excellent hemostatic performance.
[0062] The parts of the embodiments herein that are not exhaustive of the midpoint values of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.
[0063] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
[0064] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A high-strength antibacterial hemostatic chitosan hydrogel dressing, characterized in that: The hydrogel dressing raw materials include vinyl cerium oxide nanoparticles and methacryloyl chitosan in a mass ratio of 1:(20-200).
2. A high-strength antibacterial hemostatic chitosan hydrogel dressing according to claim 1, characterized in that: The preparation method of vinyl cerium oxide nanoparticles comprises the following steps: dissolving cerium nitrate hexahydrate in a solvent and heating it, then adding ammonia water to obtain a cerium oxide dispersion, then adding vinyl triethoxysilane to react, and finally washing and cooling to obtain vinyl cerium oxide nanoparticles.
3. A high-strength antibacterial hemostatic chitosan hydrogel dressing according to claim 2, characterized in that: The amount of vinyltriethoxysilane added is 0.1-10.0 ml of vinyltriethoxysilane per gram of cerium nitrate hexahydrate.
4. A high-strength antibacterial hemostatic chitosan hydrogel dressing according to claim 2, characterized in that: The reaction temperature is 50-70°C and the reaction time is 10-30 minutes.
5. A high-strength antibacterial hemostatic chitosan hydrogel dressing according to claim 1 or 2, characterized in that: The particle size of the vinyl cerium oxide nanoparticles is 100-800 nm.
6. The high-strength antibacterial hemostatic chitosan hydrogel dressing according to claim 1, characterized in that: Methacryloyl chitosan is prepared by reacting chitosan with methacrylic anhydride to carry out double bond functionalization modification.
7. A high-strength antibacterial hemostatic chitosan hydrogel dressing according to claim 6, characterized in that: The viscosity of chitosan is 100-200 mPa s, and the degree of deacetylation is ≥95%.
8. The high-strength antibacterial hemostatic chitosan hydrogel dressing according to claim 6, characterized in that: The double bond grafting rate of methacryloyl chitosan is 5-20%.
9. A method for preparing the high-strength antibacterial hemostatic chitosan hydrogel dressing as claimed in claim 1, characterized in that: The method comprises the following steps: S1, dissolving methacryloyl chitosan and a photoinitiator in water to obtain a methacryloyl chitosan aqueous solution; S2, then ultrasonically dispersing the vinyl cerium oxide nanoparticles into a mixed solution of water and an organic solvent to obtain a vinyl cerium oxide nanoparticle mixed solution; S3, stirring the methacrylylated chitosan aqueous solution and the vinyl cerium oxide nanoparticles mixed solution uniformly and then introducing nitrogen gas into the mixed solution to obtain a prepolymer solution; S3, photocuring the prepolymer solution to obtain chitosan hydrogel.
10. The method for preparing a high-strength antibacterial hemostatic chitosan hydrogel dressing according to claim 9, characterized in that: The mass ratio of the photoinitiator to the methacrylylated chitosan is 0.1-1:100.
Citation Information
Patent Citations
Preparation method of high-strength methacrylation chitosan hydrogel
CN109627462A
Nanometer hybridized hydrogel with durable broad spectrum antibacterial performance and preparation method thereof
CN101658485A
Photopolymerizable chitosan derivatives, their preparation methods and applications
CN102276755A
Quickly UV (ultraviolet) curable and water soluble chitosan derivative and synthesis method thereof
CN103333272A
Preparation method of nano-composite hydrogel and application of nano-composite hydrogel in promoting healing of diabetic wounds
CN113956413A
Cited By
Photopolymerization antibacterial hydrogel patch and preparation method thereof
CN122163860A